Impact of Environmental Regulation on Coastal Marine Pollution—A Case of Coastal Prefecture-Level Cities in China - Ma, Jintao; Hu, Qiuguang; Wei, Xinyi (Frontiers in Marine Science, 2022)
Based on the data on the level of environmental regulation and the degree of coastal marine pollution in 46 coastal prefecture-level cities in China from 2004 to 2016, this study uses the mediation effect model and the spatial Durbin model to analyze the impact and role of environmental regulation on offshore pollution from multiple dimensions and mechanisms. The findings are as follows: (1) Environmental regulation has an inverted "U"-shaped nonlinear effect on coastal marine pollution, which first intensifies and then inhibits. (2) Promoting green technology innovation is an important mechanism for environmental regulation to improve the quality of the marine environment, and the impact of environmental regulation on green technology innovation is characterized by a "U" shape. (3) Environmental regulation of coastal cities can affect coastal marine pollution in adjacent areas through spatial spillover effects, and the impact trajectory also shows an inverted "U"-shaped curve. This study proposes that in the process of marine environmental governance, first, a scientific and strict environmental regulation system should be constructed, and differentiated environmental regulation policies should be implemented. Second, giving full play to the conduction effect of green technology innovation and promoting the research and development, diffusion, and application of green technology are necessary. Third, we must attach importance to the cross-regional transfer and control of offshore pollution and promote re-gional joint prevention and control work.